Capital markets integration, volatility and persistence - Aizenman, Joshua 1949- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1995)
This paper shows that volatility induces adverse first order welfare effects in countries excluded from the global capital market. This result is illustrated in a model characterized by gains from a greater division of activities, where shocks are persistent. We show that non-linearities attributed to financial autarky explain the adverse welfare effects of volatility. We identify the parameters determining the magnitude of the loss -- it is proportional to the autocorrelation of shocks, to volatility (as measured by the standard deviation of shocks), and to the degree of product differentiation (as measured by the substitutability among intermediate products).This paper shows that volatility induces adverse first order welfare effects in countries excluded from the global capital market. This result is illustrated in a model characterized by gains from a greater division of activities, where shocks are persistent. We show that non-linearities attributed to financial autarky explain the adverse welfare effects of volatility. We identify the parameters determining the magnitude of the loss -- it is proportional to the autocorrelation of shocks, to volatility (as measured by the standard deviation of shocks), and to the degree of product differentiation (as measured by the substitutability among intermediate product.